Characterisation of cytoplasmic uridyl transferases in yeast and human cells - Schmidt, M (2011)
Regulation of gene expression by terminal addition of uridyl residues to RNA substrates has recently emerged as a widespread phenomenon in eukaryotes. Studies in organisms ranging from fission yeast to human cells have shown that uridylation of RNA 3' ends stimulates rapid RNA degradation. However, many questions regarding the specificity of the uridyl transferases, the broad range of their substrates and the consequences of their loss are still unanswered. In light of this, the uridyl transferases Cid1 in Schizosaccharomyces pombe and ZCCHC11 in human cells and their roles in the regulation of gene expression were further characterised in this study. To begin with, the biochemistry of the Cid1 protein complex responsible for uridylation in Schizosaccharomyces pombe was analysed in more detail by mass spectrometry and in vitro assays. These experiments provided insights into the modulation of Cid1 activity by accessory factors. Next, the role of the human uridyl transferase ZCCHC11 in the regulation of replication- dependent histone mRNAs was examined. Results showed that ZCCHC11 is required for efficient destabilisation of histone mRNAs following inhibition or completion of DNA replication. In agreement with this finding, cDNA sequencing experiments showed that ZCCHC11-mediated uridylation is particularly prevalent at the end of S phase. Finally, this thesis also explored the phenotype resulting from ZCCHC11 knock-down with respect to the human cell cycle. Depletion of ZCCHC11 led to the occurrence of DNA damage and activation of the DNA integrity checkpoint, which in turn resulted in cell cycle delay. Taken together, the data presented in this thesis extend current knowledge of the uridyl transferases and their actions in fission yeast and human cells and provide a link between RNA regulation and cell cycle control.